Karakteristik Penyakit Kulit dan Kelamin pada Penderita Infeksi Human Immunodeficiency Virus di Rumah Sakit Umum Daerah Buleleng: Characteristics Of Skin And Venereal Diseases In Patients With Human Immunodeficiency Virus (HIV) Infection At Buleleng General Hospital - Supradnyan, I Komang Harry; Wijaya, I Made Kusuma; Wibawa, Ketut Suteja (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Introduction: Various skin and venereal diseases have been linked to HIV infection. This disease can be specifically related to HIV, but it can also be a common disease but with more severe manifestations and more difficult to treat. Objective: To determine the characteristics of skin and venereal diseases in patients with HIV infection at the Buleleng Regional General Hospital. Methods: a cross-sectional study approach carried out in the period May 2023 to July 2023. The diagnosis of HIV infection was proven by laboratory examination, meanwhile the diagnosis of the disease skin and genitalia are confirmed clinically by a skin and genital specialist, and if necessary, supporting examinations are carried out. Results: There were 28 HIV patients with complaints of skin and venereal diseases. The number of male patients compared to female is 2.1:1 with a predominance in the age group 31-40 years. Most of the patients are at stage 4 and the most common route of transmission is through free sex and homosexuality. There were 49 diagnoses in the field of skin and genitals from the 28 patients examined. The characteristics of skin and venereal diseases in patients were 57.1% diagnosed with infectious diseases, the rest were non-infectious diseases. Conclusion: Infectious diseases include bacterial infections (syphilis, ecthyma, granuloma inguinale, bartholinitis and impetigo crustosa), viral infections (herpes zoster, condyloma acuminata, molluscum contagiosum and herpes labialis) and fungal infections (oroesophageal candidiasis, oral candidiasis and angular cheilitis). Meanwhile, non-infectious cases consist of seborrheic dermatitis, papular pruritic eruption and drug eruption.